Insights into the microbial life in silica-rich subterranean environments: microbial communities and ecological interactions in an orthoquartzite cave (Imawarì Yeuta, Auyan Tepui, Venezuela) - Ghezzi, Daniele; Foschi, Lisa; Firrincieli, Andrea; Hong, Pei-Ying; Vergara, Freddy; De Waele, Jo; Sauro, Francesco; Cappelletti, Martina (Frontiers in Microbiology, 2022)
Microbial communities inhabiting caves in quartz-rich rocks are still underexplored, despite their possible role in the silica cycle. The world’s longest orthoquartzite cave, Imawarì Yeuta, represents a perfect arena for the investigation of the interactions between microorganisms and silica in non-thermal environments due to the presence of extraordinary amounts of amorphous silica speleothems of different kinds. In this work, the microbial diversity of Imawarì Yeuta was dissected by analyzing nineteen samples collected from different locations representative of different silica amorphization phases and types of samples. Specifically, we investigated the major ecological patterns in cave biodiversity, specific taxa enrichment, and the main ecological clusters through co-occurrence network analysis. Water content greatly contributed to the microbial communities’ composition and structures in the cave leading to the sample clustering into three groups DRY, WET, and WATER. Each of these groups was enriched in members of Actinobacteriota, Acidobacteriota, and Gammaproteobacteria, respectively. Alpha diversity analysis showed the highest value of diversity and richness for the WET samples, while the DRY group had the lowest. This was accompanied by the presence of correlation patterns including either orders belonging to various phyla from WET samples or orders belonging to the Actinobacteriota and Firmicutes phyla from DRY group samples. The phylogenetic analysis of the dominant species in WET and DRY samples showed that Acidobacteriota and Actinobacteriota strains were affiliated with uncultured bacteria retrieved from various oligotrophic and silica/quartz-rich environments, not only associated with subterranean sites. Our results suggest that the water content greatly contributes to shaping the microbial diversity within a subterranean quartzite environment. Further, the phylogenetic affiliation between Imawarì Yeuta dominant microbes and reference strains retrieved from both surface and subsurface silica- and/or CO2/CO-rich environments, underlines the selective pressure applied by quartz as rock substrate. Oligotrophy probably in association with the geochemistry of silica/quartz low pH buffering activity and alternative energy sources led to the colonization of specific silica-associated microorganisms. This study provides clues for a better comprehension of the poorly known microbial life in subsurface and surface quartz-dominated environments.